Penerapan model pembelajaran kooperatif tipe team accelerated instruction untuk meningkatkan hasil belajar bahasa Indonesia - Filipe da Costa Meneses (Indonesian Journal of Educational Development, 2020)
This research is a classroom action research which aims to determine the extent to which the application of the Team Accelerated Instruction (TAI) cooperative learning model can improve Indonesian learning outcomes. The research subjects were students of class XI MIPA-1 SMA Negeri 1 Marga semester 2 of the 2018/2019 academic year consisting of 32 students. The object of research is the result of learning Indonesian at KD 3.13 Analyzing the content, systematics and language of a proposal and 4.13 Designing a scientific work proposal by paying attention to the information, objectives, and essence of the scientific work needed. Student learning outcomes data were collected using learning outcome tests. The data analysis was conducted in a descriptive qualitative manner. This action research is said to be successful if it meets the following criteria: (1) a minimum grade average score of 68 and (2) a minimum classical completeness of 85%. The results showed that in the first cycle the class average value was 67.88, increasing in the second cycle to 74.69; while classical completeness increased from cycle I of 81.25% to 90.63% in cycle II. Thus this action research was successfully carried out in 2 cycles. Penelitian ini merupakan penelitian tindakan kelas yang bertujuan untuk mengetahui sejauh mana penerapan model pembelajaran kooperatif tipe Team Accelerated Instruction (TAI) dapat meningkatkan hasil belajar bahasa Indonesia. Subjek penelitian adalah siswa kelas XI MIPA-1 SMA Negeri 1 Marga semester 2 Tahun Pelajaran 2018/2019 terdiri dari 32 orang siswa. Objek penelitian adalah hasil belajar bahasa Indonesia pada KD 3.13 Menganalisis isi, sistematika, dan kebahasaan suatu proposal dan 4.13 Merancang sebuah proposal karya ilmiah dengan memerhatikan informasi, tujuan, dan esensi karya ilmiah yang diperlukan.Data hasil belajar siswa dikumpulkan menggunakan tes hasil belajar. Analisis data dilakukan secara deskriptif kualitatif. Penelitian tindakan ini dikatakan berhasil bila memenuhi kriteria sebagai berikut: (1) nilai rata-rata kelas minimal 68 dan (2) ketuntasan klasikal minimal 85%. Hasil penelitian menunjukkan bahwa pada siklus I nilai rata-rata kelas sebesar 67,88  meningkat pada siklus II menjadi 74,69; sedangkan ketuntasan klasikal meningkat dari siklus I sebesar 81,25% menjadi 90,63% pada siklus II. Dengan demikian penelitian tindakan ini berhasil dilaksanakan dalam 2 siklus.